2009
DOI: 10.1021/mp800119h
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PLGA Nanospheres Stabilized with Amphiphilic Polymers: Hydrophobically Modified Hydroxyethyl Starch vs Pluronics

Abstract: Some Pluronics, particularly F127, are known to stabilize nanospheres and prolong their circulation time in vivo. However, these copolymers of poly(ethylene glycol) (PEG) and poly(propylene glycol) are not biodegradable, and despite the long history, there is no approved commercial product using F127 for parenteral administration until now. Meanwhile, hydroxyethyl starch (HES) is a biodegradable polymer that is currently investigated as a substitute for PEG. In order to produce a fully biodegradable amphiphili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 37 publications
(47 reference statements)
0
48
0
2
Order By: Relevance
“…[14][15][16][17] However, the potential drawback of using Pluronics is the nondegradability and lack of renal excretion for high-molecular-weight members of this copolymer class. 18,19 Previous work by our group has demonstrated that a very low-molecular-weight MePEG-b-PCL copolymer (MePEG 17 -b-PCL 5 [PCL5]) is an effective modulator of P-gp. We reported on the ability of PCL5 used at concentrations above and below the critical micelle concentration (0.03%) to enhance the accumulation of Pgp substrates, including PTX, in P-gp-overexpressing cell.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] However, the potential drawback of using Pluronics is the nondegradability and lack of renal excretion for high-molecular-weight members of this copolymer class. 18,19 Previous work by our group has demonstrated that a very low-molecular-weight MePEG-b-PCL copolymer (MePEG 17 -b-PCL 5 [PCL5]) is an effective modulator of P-gp. We reported on the ability of PCL5 used at concentrations above and below the critical micelle concentration (0.03%) to enhance the accumulation of Pgp substrates, including PTX, in P-gp-overexpressing cell.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in ZP with an increase in the thickness of the adsorbed polymer layer is due to the outward shift of the slipping plane, at which ZP is measured. 50 According to Gouy-Chapman theory, the slipping plane is moved to a point further out from the surface where the charge density is much smaller than on the surface resulting in lower ZP. This explains the lower ZP (as an absolute value) of Pluronic F127 nanosuspensions (having higher thickness of adsorbed polymer layer due to higher number of PEO units) compared with Pluronic F68 nanosuspensions (Table 1; Figure 3C).…”
mentioning
confidence: 99%
“…Differences observed between F68 and F127 could also be related to the small molecular weight of the PEG chains presented in F68 (approximately 4000 g/mol for F68 and 5000 g/mol for F127). In other studies, F68-coated particles shown higher uptake by macrophages when compared to F127-coated particles (60,61). Regarding F108 micelles, size appears to be the main responsible for the higher uptake compared to F127 micelles.…”
Section: Accepted Manuscriptmentioning
confidence: 65%